ANALYSIS ABSORPTION OF ENGLISH LEARNING MATERIALS IN E-LEARNING - Wahyu Brahma, A.A. Gede Raka; PramithaR, Gede Dana (Universitas Pendidikan Ganesha, 2021)
Communication science is very important in supporting the activities of the world community. Nowadays one must be able to speak English to compete. Some students stated that the absorption and understanding of English vocabulary on technology materials and sentence structure were limited. This has an impact on students' low English skills. The purpose of this study is to analyze the absorption of English learning materials in E-learning. This type of research is qualitative. Data collection techniques used in this study were interviews, Documentation Studies. The types and sources of data in this study are primary and secondary data. The technique used to analyze the data is descriptive qualitative and quantitative. The result of the research is that after learning English is done by E-learning, it is easier for students to understand English learning because E-learning can allow students to learn anywhere and students can understand English learning materials easily. This research implies that the use of E-learning in learning English will improve students' understanding of learning so that it impacts increasing student learning outcomes.